Application of polycapillary optics for dual energy spectroscopy based on a laboratory source; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 402 - Cherepennikov Yu. M. Yuriy Mihaylovich; Miloichikova I. A. Irina Alekseevna; Gogolev A. S. Aleksey Sergeevich; Stuchebrov S. G. Sergey Gennadevich; Hampai D. Darjyush; Dabagov S. B. Sultan Barasbievich; Liedl A. (2017, 2017)
Title screen